Violência doméstica no ordenamento jurídico brasileiro: em busca de mecanismos legais para a maior efetividade da Lei 11.340/2006 - Pôrto, Rúbia Cristina (2018)
After more than 12 years of creation of law 11.340 / 2006, the number of domestic and family violence cases is increasing and becoming increasingly serious. There are significant advances in the awareness of society about the issue, but the situation of women is still very vulnerable. The time between the communication of violence to the police authority and the hearing of justification, the withdrawal without any consequence for the aggressor and the absence of typification of psychological violence are obstacles that hamper the performance of the State. The objective is not only to punish, but mainly, to re-educate the aggressors and consequently the society, removing prejudices about the themes that involve gender equality, among them domestic violence. Through a bibliographic review and analysis of statistical data, the present work presents a proposal to create mechanisms that aim at greater effectiveness of the law in question.